The effect of westerlies on East African rainfall and the associated role of tropical cyclones and the Madden–Julian Oscillation. (15th December 2019) - Finney, Declan L.; Marsham, John H.; Walker, Dean P.; Birch, Cathryn E.; Woodhams, Beth J.; Jackson, Lawrence S.; Hardy, Sam
Abstract: Variability of rainfall in East Africa has major impacts on lives and livelihoods. From floods to droughts, this variability is important on short daily time‐scales to longer decadal time‐scales, as is apparent from the devastating effects of droughts in East Africa over recent decades. Past studies have highlighted the Congo airmass in enhancing East African rainfall. Our detailed analysis of the feature shows that days with a westerly moisture flow, bringing the Congo airmass, enhance rainfall by up to 100% above the daily mean, depending on the time of year. Conversely, there is a suppression of rainfall on days with a strong easterly flow. Days with a westerly moisture flux are in a minority in all seasons but we show that long rains with more westerly days are wetter, and that during the most‐recent decade which has had more frequent droughts (associated with the "Eastern African climate paradox"), there has been few days with such westerlies. We also investigate the influence of the Madden–Julian Oscillation (MJO) and tropical cyclones, and their interaction with the westerly flow. We show that days of westerly moisture flux are more likely during phases 3 and 4 of the MJO and when there are one or more tropical cyclones present. In addition, tropical cyclones are more likely to form during these phases of the MJO, and more likely to be coincident with westerlies when forming to the east of Madagascar. Overall, our analysis brings together many different processes that have been discussed in the literature but not yet considered in complete combination. The results demonstrate the importance of the Congo airmass on daily to climate time‐scales, and in doing so offers useful angles of investigation for future studies into prediction of East African rainfall. Abstract : Westerly moisture flux from the Congo across East Africa enhances rainfall. This can occur during favourable phases of the Madden‐Julian Oscillation, and is enhanced by the presence of tropical cyclones in the Indian Ocean. The variability in the formation of these westerlies is an important factor for East African long rains variability. The figure shows mean difference of atmospheric state on days with westerly moisture flux compared to days with an easterly flux for (a) column‐integrated westerly moisture flux, (b) precipitation, (c) mean sea level pressure and (d) relative vorticity. Relative vorticity is positive for cyclonic activity in the Northern Hemisphere, and negative for cyclonic activity in the Southern Hemisphere